Agouti Related Peptide Secreted Via Human Mesenchymal Stem Cells Upregulates Proteasome Activity in an Alzheimer’s Disease Model - Lee, Na Kyung (Sci Rep, 2017)
The activity of the ubiquitin proteasome system (UPS) is downregulated in aggregation diseases such as Alzheimer’s disease (AD). In this study, we investigated the therapeutic potential of the Agouti-related peptide (AgRP), which is secreted by human mesenchymal stem cells (MSCs), in terms of its effect on the regulation of proteasome activity in AD. When SH-SY5Y human neuroblastoma cells were co-cultured with MSCs isolated from human Wharton’s Jelly (WJ-MSC), their proteasome activity was significantly upregulated. Further analysis of the conditioned media after co-culture allowed us to identify significant concentrations of a neuropeptide, called AgRP. The stereotactic delivery of either WJ-MSCs or AgRP into the hippocampi of C57BL6/J and 5XFAD mice induced a significant increase of proteasome activity and suppressed the accumulation of ubiquitin-conjugated proteins. Collectively, these findings suggest strong therapeutic potential for WJ-MSCs and AgRP to enhance proteasome activity, thereby potentially reducing abnormal protein aggregation and delaying the clinical progression of various neurodegenerative diseases.